Business Plan-CHOI Weight Loss Consultancy - CAI, PANPAN (2017)
This is a business plan of CHOI Weight Loss Consultancy which documents the overall information concerning creation of this startup. The new status of China that it has the largest population in the world has catch Chinese government attention as well as Chinese people. China now is home to 43.2 million obese men and 46.4 million obese women. Obesity has been a growing program in the country due to modern convenient life. The central government has brandished a plan called Healthy China 2030, with the aim of making China healthy again in the next 13 years. However, the programmes of current weight loss market have less focuses on providing sustainability, education and psychological help. With the purposes to solve those problems, this business plan aims to provide service of sustainable and effective weight loss approach for Chinese female in today’s modern busy life. One of the founders Luyi, as a weight management consultant in the industry for years, she is passionate in helping overweight people. Siyi, with relevant working experience in marketing and most importantly, used to be struggling to lose weight which makes her full of passion to engage in this industry. The service of CHOI is a 28-day online service programs based on WeChat that consist of personal health information analysis, diet and meal plan, workout plan, peer company, meal and exercise supervision, courses on health and nutrition knowledge, psychological help, plan adjustment and maintenance. The service focus on providing courses of nutrition courses and providing encouragement to help people form healthy habits. In order to achieve this, hiring experienced consultant teams which includes fitness trainer, dietician, consultant psychologist, weight management consultants and doctor is at the heart of business concerns that competencies should include solid academic background and rich practical experienced. Moreover, hiring high-qualified programme leaders is also another key strategy of CHOI. In addition to this, implementing effective digital marketing is a main marketing strategy to increase the brand awareness with less cost. The service will be designed within 3 months and will be launched in July 2018. It is estimated that the company will start to earn positive profits in fourth quarter. After then, the profits will continue to growth and reach RMB 180,410 (GBP 20,045) in year 3 quarter 4. We believe that CHOI will become the most reliable online weight management consultant in China and lead Chinese female to wellbeing.